2022
DOI: 10.30736/voj.v4i2.616
|View full text |Cite
|
Sign up to set email alerts
|

Model ARIMA-GARCH pada Data Kurs JISDOR selama Masa Pandemi COVID-19

Abstract: Kurs JISDOR selama pandemi COVID-19 berpengaruh terhadap perekonomian Indonesia, sehingga tujuan penelitian ini adalah memodelkan data kurs JISDOR selama pandemi. Model dibentuk mengikuti sifat- sifat yang dimiliki data tersebut. Data memiliki tren dan non stasioner, maka data di differencing 1, menjadi stasioner setelah di uji ADF. Kemudian sesuai plot ACF, PACF, nilai minimum AIC dan SIC didapatkan model yang tepat adalah ARIMA(1,1,1). Model ini memiliki heteroscedasticity, maka dilanjutkan membentuk model A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Telekomunikasi Indonesia's stock data. Putri, Zukhronah, & Pratiwi (2021), cited in (Rakhmawati et al, 2022), The research (Farosanti https://ejournal.staim-tulungagung.ac.id/index.php/eksyar Volume 10, Issue 1, 2023 et al, 2022) proved to be quite successful with the ARIMA (4,2,1) model on the sales data of medical and laboratory equipment at PT, which indicated that an ARIMA model containing heteroscedasticity does not meet the assumptions of the ARIMA model. Heteroscedasticity occurs when the residual variance in time series data is not constant, necessitating a combination of ARIMA and GARCH models.…”
Section: Introductionmentioning
confidence: 99%
“…Telekomunikasi Indonesia's stock data. Putri, Zukhronah, & Pratiwi (2021), cited in (Rakhmawati et al, 2022), The research (Farosanti https://ejournal.staim-tulungagung.ac.id/index.php/eksyar Volume 10, Issue 1, 2023 et al, 2022) proved to be quite successful with the ARIMA (4,2,1) model on the sales data of medical and laboratory equipment at PT, which indicated that an ARIMA model containing heteroscedasticity does not meet the assumptions of the ARIMA model. Heteroscedasticity occurs when the residual variance in time series data is not constant, necessitating a combination of ARIMA and GARCH models.…”
Section: Introductionmentioning
confidence: 99%